Evaluating EU-Region level innovation readiness: A longitudinal analysis using principal component analysis and a constellation graph index approach - Paul Jones (Journal of Business Research, 2023)
Innovation is a component of economic development, with an emphasis on entrepreneurship and small business activity. This longitudinal study evaluates innovation readiness drivers across European regions. The following research questions are posed: What are the sets of innovation drivers in Europe? What is their relative importance? How do they differ between regions over time? The study uses principal component analysis (PCA) and the constellation graph index approach. Three principal component drivers of innovation are identified: innovation system, absorptive capacity, and IP protection. The aggregation of component details reveals an innovation readiness dimension for each European region in a specific year. Variations in results for different years are discussed. The study covers a large number of countries. Innovation readiness across regions is examined. The results show that constituent innovation driver variables contribute to performance over time. Different patterns are revealed for high and low innovation regions. The relationships between innovation drivers are evaluated.